Patrimônios (in) visíveis da Fundação Museu Couros em Formosa/GO : patrimônio cultural, educação patrimonial e experiências narrativas - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This technical report aims to present and analyze the Fundação Museu Couros de Formosa/GO (FUMUC) as Cultural Heritage of the city. The choice of this space as an object of study came from its collection, which contains historical items and because it provides repertoires of memories and narratives of the people from Formosa. The research involves a documentary analysis that approaches everything from historical relations with the city to the institutionalization of FUMUC as a possible local heritage, highlighting the significance and memory of this space for the community, providing this population with the opportunity to dialogue with the collection through the narratives of their experiences, life experiences and memories. To achieve this, we use a methodology based on bibliographical studies, establishing discussions about Cultural Heritage, Heritage Education and Identity. We also propose action research characterized by technical visits to the museum. The problematics involved in the research is articulated around its owner, Mr Leônidas, through the biographical profile that the space is built around this character. Thus, based on dialogue with its founder, and the observation and study of museum items and interviews with Formosan residents, we aim to build an institutional website as the final product of this report. The difference between this site is the possibility of community participation through reports of experiences they may have with the objects, that is, a site that can be interactive and informative. It should be noted that this research aims to contribute to the improvement and preservation of Formosan cultural references, opening up new possibilities for studies on the subject.
(In)visible heritage of the Couros Museum Foundation in Formosa/GO : cultural heritage, heritage education and narrative experiences
Keywords: Patrimônio cultural; Memória; Identidade; FUMUC; Educação patrimonial; Cultural heritage; Memory; Identity; Heritage education; CIENCIAS HUMANAS::HISTORIA